ALGORITIM TUSHUNCHASINI O‘RGANISH (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
In this article, the young people of Uzbekistan, who are being updated, can use the knowledge they are getting today in their daily activities, and the ways to step by step achieve their goals.